Quantitative Assessment of Chronotropic Incompetence Using Time Domain Heart Rate Variability Derived from 24 – Hours Ambulatory Holter Monitoring - Ardian Rizal; Fitranti Suciati Laitupa; Mohammad Saifur Rohman (Heart Science Journal, 2020)
Background : Chronotropic incompetence (CI) is defined as the failure of the heart to increase its heart rate along with activity and is an independent predictor of cardiovascular morbidity and mortality. The gold standard for CI is based on a treadmill test. However, up to now, there is no guideline to recommend whether CI could be concluded according to holter monitoring data.Objective : This study aimed to determine CI based on Holter monitoring, specifically using time-domain analysis of heart rate variability (HRV).Methods : This study used descriptive-analytic research with cross-sectional sampling. The population was patients that underwent treadmill and holter monitoring. The treadmill test was used as a gold standard of CI, and compare to holter monitoring using heart rate variability as a parameter. Data analysis used a comparative study (Independent T, Mann-Whitney, Chi-Square) and multivariate analysis logistic regression with a significance of p < 0,05.Results: The subjects of the study were 111 patients with male-dominant (59 men). Standard Deviation N-N interval (SDNN) and Standard Deviation of Average N-N Interval (SDANN) were found lower in the CI group compared to the normal one. Mean SDNN was 113,57 + 51,08 msec in CI group and 117,4 + 39,48 msec in normal group with p = 0.282. Mean SDANN was 94,77 (73,42-118,85) in CI and 104,16 (74,9–139) with p = 0.422. While the Proportion of RR interval with the difference > 50 ms (RR50) and Average of All N-N Intervals (AVNN) found to be higher in CI group, but not statistically significant (p = 0.681; p = 0.061 respectively). Other parameter extracted from holter result, delta HR showed significant correlation with CI (50.5 (43,25-61,5) vs. 56 (50-72) with p = 0.014).Conclusion: Time-domain HRV didn’t had a significant correlation with CI. However, delta HR from holter monitor could be used as a predictor of CI.